Conservation of Food, Medicinal and Dyes Crops Based on Local Community Wisdom in Mareje Village, West Lombok - Jupri, Ahmad; Isrowati, Isrowati; Anggraeni, Marsella; Pibiputri, Heppy Tasya; Riski, Tita Nia Ananda; Darussalam, Abdul Azis; Mutma’innah, Elfira; Apriadi, Rhandy Asmi; Yulianti, Yulianti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Mareje Village, located in Sheet District, West Lombok Regency, NTB, Indonesia, is one of five villages and sub-districts in the Sheet District area. Nature protection is carried out to care for and protect natural resources, including flora, fauna, ecosystems and the environment. It involves a series of actions to ensure the sustainability and balance of ecosystems and natural habitats. This research aims to identify various food, medicinal and dye plants that have long been part of the conservation practices of the Mareje Village community. The research method used is descriptive qualitative, with data collected through trusted online sources, as well as interviews and questionnaires with local residents. The research results show that the people of Mareje Village still rely on various plants as a source of food, dyes and medicine. This includes rice, corn, cassava, taro, long beans, peanuts, green beans, and sweet potatoes for food; turmeric, pandan, katuk leaves, butterfly pea flowers, and dragon fruit for coloring; as well as white binahong, cat's whiskers, castor leaves, Chinese betel leaves, katuk leaves, black turmeric, bridal flowers, and horsewhip for medicine.